Analisis Kendala dan Solusi Peningkatan Pembelajaran PAI melalui Penggunaan Microsoft PowerPoint - Nurlisa, Nurlisa; Setiawati, Beti (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research aims to understand students' preferences regarding the use of PowerPoint in Islamic Religious Education (PAI) and to identify potential challenges. The 3D development paradigm is employed, with the "Define" stage for issue identification, "Design" for crafting the questionnaire guidelines, and "Develop" for implementing solutions. Data were collected through an online questionnaire involving 10th-grade PAI students at SMKN 1 Cempaga Hulu. Research findings indicate that the majority of students (51.7%) enjoy PAI learning, with 44.8% expressing strong enthusiasm. Nevertheless, 44.8% find PAI learning challenging, particularly in topics related to banking and insurance. A significant portion of students (58.2%) still relies on textbooks as their primary learning medium, but 55.2% agree or strongly agree with the use of PowerPoint in PAI instruction. The discussion highlights that despite students' interest in PAI, difficulties persist in comprehending certain topics. Integrating PowerPoint as an alternative instructional medium can enhance the quality of learning and capture students' interest. However, prudent management is required to optimize student learning outcomes. Recommendations involve developing teaching strategies that effectively incorporate technology to enhance students' understanding of PAI content.